2012
DOI: 10.1038/pr.2012.126
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in hypoxia response genes influence hypertrophic cardiomyopathy phenotype

Abstract: Background: Risk factors for diastolic dysfunction in hypertrophic cardiomyopathy (hcM) are poorly understood. We investigated the association of variants in hypoxia-response genes with phenotype severity in pediatric hcM. Methods: a total of 80 unrelated patients <21 y and 14 related members from eight families with hcM were genotyped for six variants associated with vascular endothelial growth factor a (VEGFA) downregulation, or hypoxia-inducible factor a (HIF1A) upregulation. associations between risk genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Myocardial ischemia is previously suggested as an important complication in HCM [38] and supported by a previous mouse model of HCM [40] where sarcomere mutation-positive animals were found to upregulate genes involved in extracellular matrix remodeling in early stage of the disease, prior to the onset of histological changes characteristic for LVH and fibrosis. A human study [41] recently showed genetic variations in angiogenic and hypoxia-responsive genes with the association to younger age at diagnosis, diastolic dysfunction, and greater septal hypertrophy [41]. Although ICTP showed no correlation with any of the above CMR indices, there was an inverse relationship of myocardial perfusion during adenosine hyperemia with both LVM and mitral E/e′, a finding that strengthens the concept that myocardial perfusion abnormalities occur in parallel with the progression of myocardial hypertrophy and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial ischemia is previously suggested as an important complication in HCM [38] and supported by a previous mouse model of HCM [40] where sarcomere mutation-positive animals were found to upregulate genes involved in extracellular matrix remodeling in early stage of the disease, prior to the onset of histological changes characteristic for LVH and fibrosis. A human study [41] recently showed genetic variations in angiogenic and hypoxia-responsive genes with the association to younger age at diagnosis, diastolic dysfunction, and greater septal hypertrophy [41]. Although ICTP showed no correlation with any of the above CMR indices, there was an inverse relationship of myocardial perfusion during adenosine hyperemia with both LVM and mitral E/e′, a finding that strengthens the concept that myocardial perfusion abnormalities occur in parallel with the progression of myocardial hypertrophy and diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 70% of all patients with HCM die suddenly (Maron et al, 1995 ; Ho et al, 2010 ; Namboodiri and Francis, 2010 ; Alkon et al, 2012 ). The high arrhythmic propensity in HCM is due to the combination of the abnormal substrate, like fibrosis, and ischemia or hypoxia (Alkon et al, 2012 ), in general associated with intense physical exercise. Extreme physical exercise may induce, in HCM patients, diastolic pressure and volume overload of the ventricles, and hypoxemia, i.e., low oxygen saturation in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that VEGF is an endothelial cell-specific mitogen in vitro and an angiogenic inducer in in vivo models [ 15 ] and plays an important role in myocardial hypertrophy [ 16 ]. In our study, we confirmed increased serum VEGF level in patients with nonobstructive HCM when compared to normal population.…”
Section: Discussionmentioning
confidence: 99%